Upaya Direktorat Kepolisian Perairan dan Udara (DITPOLAIRUD) Polda Nusa Tenggara Timur dalam Menangani Tindak Pidana Konservasi Sumber Daya Alam - Maria Sisilia Maukelen; Setiyono Setiyono; Teguh Suratman; Susianto susianto (University of Merdeka Malang, 2020)
The number of cases of natural resource conservation crimes that continue to occur every year, both those that have been decided, and those that have not received a court ruling in the jurisdiction of East Nusa Tenggara Province, and even those that repeat the same crimes, is very inviting a lot of attention from the community. Based on Article 33 paragraph (3) of the Constitution of the Republic of Indonesia year 1945, which in essence confirms that all kindsof natural resources on the earth indonesia is controlled or managed by the state with the aim of providing the most prosperity for the community. But the fact that occurred is the arrest and trade of hawksbill turtles (Eretmochelys imbrata) that occurred in the waters of West Kupang, East Nusa Tenggara quite seized a lot of attention from both law enforcement and the general public. It is because from 2016 until the end of 2017 there were about 11 turtles (Eretmochelys imbrata) caught by fishermen where 3 hawksbill turtles were caught in theWaters of Tanjung Bunga, East Flores, and 9 other hawksbill turtles were caught in the Waters of West Kupang. From the data above the author conducted a study with empirical juridical method, namely by interviewing the Head of the Directorate of Water and Air Police (Ditpolairud) NTT Police, with the aim to analyze what are the obstacles faced in order to enforce the law against natural conservation crimes and how the next effort?